Implementation of Accreditation-Based Management Standards at the Pontianak Green Community Learning Activity Center - Muhammad Rusli Abdillah; Wahyudi Wahyudi; Sukmawati Sukmawati (JETL (Journal of Education, Teaching and Learning), 2018)
The purpose of this study is to describe the planning of accreditation-based management standards at the community learning center (PKBM) of Pondok Hijau in Pontianak and describe the planning of accreditation-based management standards at the learning center of Pondok Hijau Pontianak community. The approach used in this study is qualitative research, with ethnographic procedures, because researchers intend to explore in-depth and comprehensive information, then analyze, and interpret individual patterns or behaviors that develop over time in non-formal education units, namely PKBM. As for the object of research or data sources (informants) are: Chairperson, GTK, parents of students, figures/forums representative of the local community, Department of Education and Culture, as well as partners of education units that are used as research objects in PKBM Pondok Hijau Pontianak, and research results more emphasis on meaning than generalization. The results obtained from this study are 1) planning for the implementation of management standards has met the maximum achievement according to the PKBM unit accreditation assessment rubric; 2) implementation of management standards still need to be more intensively involved with related parties; 3) supervision ofthe implementation of management standards has not met the maximum achievement according to the accreditation guidelines; and 4) reports on the implementation of management standards meet the maximum achievements according to the rubric of accreditation assessment for PKBM clusters, both the results of activities and finances are reported in full per activity, submitted periodically to the relevant parties.